El efecto de valorización del capital intelectual en el patrimonio de la Caja Maynas - Iquitos periodo – 2022 - Rengifo Villacorta, Winston Jose (2024)
This study examines the impact of an intellectual capital assessment on the equity of Caja Maynas, Iquitos in the year 2022. The objective is to determine how the assessment of intellectual capital affects the equity of Caja Maynas - Iquitos. The hypothesis raised is that the evaluation of intellectual capital has a direct impact on the assets of Caja Maynas Iquitos, through its recognition and appropriate use. This is a type of descriptive correlation; A quantitative approach was adopted, using a questionnaire for data collection and survey techniques, in addition, I used reports obtained from the published Caja Maynas 2022 annual report. Source that was used in the processing of the information using SPSS vs 26, the software gives us the opportunity to draw the following conclusions: the evaluation of intellectual capital has a direct impact on the assets of Caja Maynas, identifying it and using it accordingly; through knowledge of the level of competitiveness of the Department of Economic Situation of the Loreto Region. Intellectual capital also affects economic profitability by effectively managing the company's own resources. Officials are advised to continually manage intellectual capital to improve profitability.